Towards a GSE international teaching network: Mapping Global Software Engineering courses - Fortaleza, L. L.; Conte, T.; Marczak, S.; Prikladnicki, R. (2012 Second International Workshop on Collaborative Teaching of Globally Distributed Software Development (CTGDSD), 2012)
Teaching Global Software Engineering is challenging since it is not trivial to simulate distance and the changes that distance brings into the traditional software development life cycle. Despite the challenge, the need to teach undergrad and graduate students the skills to work in such environment is well-known in academia. The goal of this paper is two-folded. First, we identify what has been thought, by whom and to whom by conducting a literature review. This review aims to consolidate the body of knowledge on the topic in order to help professors and professionals interested in teaching the subject. For instance, we found that 19 courses have been reported involving 25 countries in total since 1997. Most of the courses involves graduate students as the main audience, and mainly discuss challenges in distributed development. Our second goal is to propose the creation of a collaborative repository to store and to report teaching experiences on the topic helping the development and strengthening of the Teaching Network community.